Provocative testing using low dose oral flecainide for diagnosis of Brugada syndrome: a report of two cases. Issue 12 (12th December 2022) - Amir, Muzakkir; Kabo, Peter; Rahma, Iznaeny
Abstract: Background: Brugada syndrome (BrS) is a genetic disease characterized by coved ST-segment elevation in the right precordial leads that predispose to life-threatening ventricular tachyarrhythmia. The electrocardiographic signature is dynamic and often concealed but can be unmasked by potent sodium channel blockers such as Flecainide. Some studies have evaluated the effectivity of oral Flecainide 400 mg for provocative testing, but clinical utility of lower dose Flecainide (300 mg) has never been documented. Case summary: These two cases illustrate the effectiveness of low dose oral Flecainide to unmask Brugada electrocardiographic pattern. In our patients, diagnostic type 1 electrocardiography started to develop 30 min after drug administration and reached maximal positivity at 3.5–4.5 h. No atrioventricular block or ventricular arrhythmia was observed during the procedures. Discussion: A potent sodium channel blocker facilitates marked reduction of the right ventricle epicardial action potential, which creates a transmural voltage dispersion and manifests as an ST elevation in the right precordial leads. Time to positivity was comparably rapid, and time to maximal ST-elevation appeared close to peak plasma level of Flecainide (ranging from 1 to 6 h). Although asymptomatic patients have a low rate of adverse cardiac events, it is crucial to inform patients to avoid various modulators and precipitating factors that could trigger malignant arrhythmias.